Performing: standard operating procedures - Rautalahti, Katariina (Henry Stewart Talks, 2012)
Reasons for having SOPs, Requirements needed for SOP systems to comply with OECD principles, SOP requirements for sponsors, e-SOPs, Field Studies, Multi-site studies, How to inspect SOPs